A contribution to a generic revision of Simochromis and Tropheus (Pisces : Cichlidae) - from Lake Tanganyika, with special reference to the Pharyngeal Apophysis and its taxonomic importance - Axelrod, Glen S (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1978)
The purpose of this thesis is to investigate the taxonomic status of Simochromis and Tropheue. Material for the study wae collected during three visits to Lake Tanganyika in 1976-1977. Tropheus polli G. S . Axelrod 1977, was found and described, and a new species of Simochromis was found and will be described in a forthcoming paper. Nine colour varieties of Tropheus maorii and three colour varieties of Tropheus duboisi were found and described. A diagnosis and description, with colour photographs, is given using morphometries and meristics of the five species of Simochromis and four species of Tropheus. A dissection and cleaning technique tor the pharyngeal apophysis and lower pharyngeal bone is explained, together with a method for the interpretation of relative bone composition of the pharyngeal apophysis. Photographs are included. The dentition is examined, evaluated and figured. Doubt has been cast upon the taxonomic validity of the composition of the pharyngeal apophysis as an indicator of affinity at the sub familial level. This is shown by its seeming lack of functional relationship, apparent arbitrary variation, interspecific variability in Simochromis and Tropheus, and intraspecific variability in S. diagramma and T. duboisi. Thus, the apophysis cannot be considered a reliable cichlid taxonomic characteristic at any level of classification, unless its validity is Substantiated in each instance. Furthermore, it is considered very probable that the Tropheus-Simochromis species complex is a monophyletic assemblage at the genus level, on the basis of similar dentition and mouth form, which is unique in Lake Tanganyika. It is proposed on phyletic grounds that Simochromis and Tropheus be united into the one genus Tropheus, and that Tropheus be divided into the subgenera , Tropheus (Tropheus) and Tropheus (Simochromis), along the lines of its previous division in two separate genera. Characteristics supporting this division include differences in the anal and dorsal fin meristic counts noted in the original descriptions of the genera. In addition, two modifications of the dentition were found during the course of this study which are not mentioned in any previous literature. It is considered probable, that Tropheus (Tropheus) and Tropheus (Simochromis) are monophyletic sister groups within the Tropheus complex. Pseudosimochromis Nelissen 1977 is not considered to be a taxonomically valid genus on either phyletic or gradistic grounds, and is included within Tropheus (Simochromis). The lower pharyngeal bone of T . (S.) diagramma is considered to be plesiomorphic in tooth arrangement, size and shape. A preliminary worKing hypothesis is established on the basis of the conjectures made and other available information which supports the phyletic relationship suggested by Fryer and lIes (1972). An illustration is given.
Keywords: Cichlids -- Tanganyika, Lake